Optimalisasi Program Pengembangan Guru melalui Dukungan Organisasional untuk Mendorong Guru Berkembang (Thriving) di Tempat Kerja - Hastuti, Rina; Samsudin, Wahyu Widodo; Yoga, Ika; Rohmatika, Arina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to empirically examine the effect of a teacher development program on educators’ psychological well-being, which is dichotomously conceptualized through the variables of thriving at work and emotional exhaustion. This study employed a quantitative method analysis. A total of 225 teachers who participated in the Teachers’ Transformation Program in Central Java Province, Indonesia, were asked to complete the survey developed using a purposive sampling technique. The data were analyzed using the Structural Equation Modeling with Partial Least Squares (SEM-PLS) method. The teacher’s development program is significantly and positively associated with psychological meaningfulness and thriving at work. In contrast, the efficacy of the teacher’s development program on role overload and psychological exhaustion is not statistically supported. In addition, perceived organizational support significantly moderates the effect of teachers’ development program on role overload and emotional exhaustion, while the moderating effect of school support on the relationship between teachers’ development program, psychological meaningfulness, and thriving at work is not significantly supported. This study contributes to the literature on teacher professional development, particularly in how the national teacher development program could potentially influence teachers' wellbeing (both positively and negatively). Policy makers should not only focus on improving competencies but also on managing teachers’ workload to prevent burnout in implementing the teacher development program.